THE ROLE OF ELEMENTARY SCHOOL TEACHERS IN PREPARING THE GOLDEN GENERATION THROUGH THE PANCASILA STUDENT PROFILE - Elinda Rizkasari (Universitas Muhammadiyah Ponorogo, 2022)
Education is the key to changing the world, through improving the quality of education, it is hoped that Indonesia will be able to produce a golden generation of superior character. As an effort to welcome the golden generation that is strong and has good morals, the role of teachers at the elementary school level is very crucial. As an educator for the prospective golden generation, it takes the best possible effort to prepare a golden generation who has 21st-century skills with superior character, critical thinking, creativity, innovation, communication, collaboration, and competition. The research was conducted using the library research method. One of the government's efforts to prepare the golden generation is by